Sclerosing Mesenteritis. (June 2019) - Danford, Christopher J.; Lin, Steven C.; Wolf, Jacqueline L.
Abstract : Sclerosing mesenteritis is a rare non-neoplastic disorder characterized by fat necrosis, chronic inflammation, and fibrosis typically of the small bowel mesentery. Our understanding of this disorder is limited by its rarity as well as inconsistent terminology used across the literature. While prior abdominal surgery or trauma, autoimmunity, infection, ischemia, and malignancy have been suggested to be involved in the pathogenesis of the disorder, it remains poorly understood. The clinical course of sclerosing mesenteritis is generally benign with a large proportion of patients diagnosed incidentally on imaging obtained for other indications. In a subset of patients, symptoms may arise from a mass effect on the bowel, lymphatics, or vasculature resulting in bowel obstruction, chylous ascites, or mesenteric ischemia. Symptomatic patients should be treated with a combination of corticosteroid and tamoxifen as first-line therapy based on retrospective case series and experience in other fibrosing disorders. Surgical intervention may be required in those with persistent obstruction despite conservative treatment, though complete resection of the mass is often not feasible given intimate involvement with the mesenteric vasculature. A careful use of terminology and communication between the radiologist, pathologist, and clinicians in the care of these patients will be essential to future efforts at understanding this disease.